A phosphorus-containing flame retardant with thermal feature suitable for polyamide 6 and its filaments with enhanced anti-dripping performance. (June 2022) - Sun, Yanlu; Wang, Zhengqi; Wu, Dequn; Wang, Xueli; Yu, Jianyong; Yuan, Ruchao; Li, Faxue
Highlights: A phosphorus-containing flame retardant (CBPB) with thermal feature suitable for PA6 was synthesized. The chemical cross-linking networks formed through trimerization reaction of nitrile groups were used to suppress melt-dripping of PA6. UL-94 and LOI of PA6/CBPB composites reached V-0 and 32.0% respectively when only 8 wt% of CBPB was added. The melt-spun FR-PA6 filaments remained outstanding flame retardance and enough high tenacity to weave for textile processing. Abstract: The absence of flame retardant with suitable thermal feature and high flame retardancy has greatly limited the development of flame-retardant polyamide 6 (PA6). In this work, a phosphorus-containing flame retardant (CBPB) with appropriate flame responsive nitrile groups was synthesized, and its melting temperature, cross-linking temperature and initial degradation temperature exactly matched the thermal feature of flame retardant suitable for PA6. PA6/CBPB composites (FR-PA6s) were prepared by melt-blending various contents of CBPB into PA6 matrix. The UL-94 and limiting oxygen index (LOI) of FR-PA6s reached V-0 and 32.0% respectively once 8 wt% of CBPB was added to PA6 matrix. As a representative, FR-PA6-6 (6 wt% of CBPB in PA6 matrix) was successfully melt-spun into filaments with good mechanical properties. The filament strand was self-extincted within 4 s and only one droplet was generated after ignited in the vertical burning tests. The corresponding anti-dripping and flame-retardant mechanism were also explored. Suppression of melt-dripping of FR-PA6s was formed due to the chemical cross-linking of nitrile groups of CBPB at ∼290 °C, which significantly exceeded the general processing temperature of PA6 (∼260 °C) and so the processability of FR-PA6s was slightly affected. The enhanced flame resistance of FR-PA6s was contributed to the quenching effect of PO· and PO2 · radicals as well as the diluting effect of NH3 in the gas phase.